Prevalence of beta thalassaemia/beta haemoglobin variant among thalassaemia screening in Hospital Tengku Ampuan Rahimah (HTAR), Klang - Mohyee, Norlyiyana (2020)
Introduction: Thalassaemia is the most common genetic disorders among population living in the Southeast Asia. In view of complexity and heterogeneity of the disease, hence it is difficult to diagnose the disease, especially the carriers at the health clinics. In Malaysia, thalassaemia screening program has been carry out by screening the targeted population such as pregnant women, prenuptial couples, form 4 students and family members with thalassaemia patients. In this study, the aim is to evaluate the prevalence of beta thalassaemia/ beta haemoglobin variant and its association with haematological parameters. Methodology: A cross sectional study involving secondary data collection of 4548 samples of thalassaemia screening that sent to Hospital Tengku Ampuan Rahimah, Klang, Malaysia in year 2014 to 2015. Majority of the samples taken from the subjects investigated for anaemia and the National Thalassaemia screening for Form 4 students. The samples were analysed for haematological parameters using Sysmex XN 9000 automated blood cell analyser (Capillarys 2; Sebia, France) and further analysed for haemoglobin fraction using CE and/or HPLC. The diagnoses made using the established standard criteria. Result: Out of 4548, 88.6% (4029) subjects had MCV < 80 fl and/or MCH < 27 pg. From this subjects group, 27.4% were suspected to have beta thalassaemia or beta haemoglobin variant. Majority were from female subjects (72.6%). The percentage of subjects according to races were predominately by Malay 86.5%, followed by other ethnic group. The most frequent type among screening populations was β thalassaemia traits (11.0%) followed by HbE traits (10.3%). Others include unknown variant (1.5%), suspected borderline HbA2 β thalassaemia (0.7%), HbE homozygous (0.5%) and HbE/β thalassaemia (0.3%). The remaining are β thalassaemia major, HbS heterozygous and HbS homozygous (2, 2 and 1 subjects respectively). The mean (SD) haematological parameters for β thalassemia trait were RBC: 5.38 (0.84), Hb: 11.04 (1.55), MCV: 64.18 (5.81), MCH: 20.70 (2.04) and RDW: 16.00 (2.19). Meanwhile for HbE traits, the mean (SD) were RBC: 4.94 (0.65), Hb: 11.98 (1.54), MCV: 73.10 (5.56), MCH: 24.36 (2.17) and RDW: 14.30 (2.10). Conclusion: This study demonstrated high prevalence of β thalassaemia/ β haemoglobin variant, meanwhile the β thalassaemia trait and HbE trait were the commonest group. This data suggests, thalassaemia screening program in our country is very beneficial and have to be improved from time to time. The awareness of the disease among community must be equally highlighted.